Both HuR and miR‐29s regulate expression of CB1 involved in infiltration of bone marrow monocyte/macrophage in chronic liver injury. Issue 3 (8th September 2019) - Chang, Na; Duan, Xianghui; Zhao, Zhongxin; Tian, Lei; Ji, Xiaofang; Yang, Lin; Li, Liying
Abstract: Bone marrow–derived monocytes/macrophages (BMMs) play a vital role in liver inflammation and fibrogenesis. Cannabinoid receptor 1 (CB1) mediates the recruitment of BMMs into the injured liver. In this study, we revealed the molecular mechanisms under CB1‐mediated BMM infiltration. Carbon tetrachloride (CCl4 ) was employed to induce mouse liver injury. In vivo, human antigen R (HuR) was upregulated in macrophages of injured liver. HuR messenger RNA (mRNA) expression was positively correlated with CB1 and F4/80 mRNA expression. Furthermore, we detected the binding between HuR and CB1 mRNA in CCl4 ‐treated livers. In vitro, HuR modulated arachidonyl‐2′‐chloroethylamide (ACEA, CB1 agonist)‐induced BMM migration by regulating CB1 expression. HuR promoted CB1 expression via binding to CB1 mRNA. ACEA promoted the association between HuR and CB1 mRNA via inducing HuR nucleoplasmic transport. In the cytoplasm, HuR competed with the miR‐29 family to improve CB1 expression and BMM migration. In conclusion, our results prove that HuR regulates CB1 expression and influences ACEA‐induced BMM migration by competing with miR‐29 family. Abstract : Arachidonyl‐2′‐chloroethylamide (ACEA, the cannabinoid receptor 1 [CB1] agonist) induces CB1 upregulation and bone marrow–derived monocytes/macrophages (BMM) migration in a human antigen R (HuR)‐dependent manner. HuR interacts with CB1 mRNA 3′‐UTR and regulates CB1 expression via competing with miR‐29 family in BMMs. Moreover, ACEA induces HuR nucleocytoplasmic transport and enhances the association between HuR and CB1 mRNA 3′‐UTR.